PO160 Atypical transverse myelitis in a patient with newly diagnosed hepatitis c: a case report and review of the literature. (1st December 2017) - Zarkali, Angeliki; Kumar, Guru; Sakel, Mohammed; Redmond, Ian; Harikrishnan, Sreedharan
Abstract : Transverse myelitis (TM) is often the first presentation of inflammatory central nervous system or systemic diseases; cause is not always identified with 30% of cases labelled idiopathic. Fourteen cases have been reported in patients with hepatitis C infection (HCV); often atypical, extensive and recurrent. We present a case and review the literature. A 60 year old right-handed engineer, previously fit, presented with sudden onset leg paraesthesiae and numbness. Few weeks later he developed progressive leg weakness, without bladder or bowel involvement. Examination showed flaccid paraparesis, hyperreflexia, and T8-sensory level. MRI showed a longitudinally-extensive non-enhancing cord lesion (T2-T9). CSF was acelular with elevated protein (0.70); oligoclonal bands were present in serum and CSF. Vasculitic screen, HIV, cryoglobulins and Aquaporin-4 were negative. HCV was positive, genotype 1a, with moderate viral load. There was no fibrosis on liver ultrasound. He received three days IV methylprednisolone with marked clinical improvement followed by weaning oral steroids. He is currently awaiting AbbVie 3D plus (paritaprevir/ombitasvir/ritonavir plus dasabuvir)with ribavirin. Isolated TM has been correlated with HCV, particularly atypical or relapsing presentations. It is uncertain whether the relationship is causal but HCV-undertreatment is linked with relapses. Underlying HCV should be considered once common causes are excluded and HCV-positive patients should be considered for treatment.